SPATIAL VARIABILITY OF NOISE GENERATED BY A SELF-PROPELLED COFFEE HARVESTER IN AN OPEN AREA - da Silva, José A. R. [UNESP]; Manzione, Rodrigo L. [UNESP]; de Oliveira, Geraldo G. [UNESP]; da Silva, Adriano B. [UNESP]; Putti, Fernando F. [UNESP] (FapUNIFESP (SciELO), 2022)
Despite the advantages in production, mechanization may expose workers to high noise levels in the work environment, which is considered one of the main causes of workrelated hearing loss. In this sense, this study aimed to analyze the spatial variability of noise generated by a self-propelled coffee harvester in an open area to define safe zones for operators and workers involved in coffee harvesting activities. The noise source used was an Electron Auto TDI self-propelled coffee harvester (model MWM D229-4), with a cabin manufactured in 2012 and a 67-hp 4-cylinder engine, working at 1200-rpm rotation. The noise level was measured by a digital decibel meter at points distributed within a regular 2.5 x 2.5 m sampling mesh (32.5 x 35.0 m area) surrounding the harvester in operation, which was configured according to the regulatory standard. Noise level spatial dependence was analyzed through geostatistics, characterizing structure and magnitude, and mapping spatial variability. Results showed that noise levels were above the limit established by relevant legislation (i.e., 85 dB), both for operators and employees at a distance of about 5.5 m from the generating source.
Keywords: Coffee harvest; Mapping; Mechanization; Occupational risk